Are farmers aware of first aid measures for their injuries-a survey in rural Karnataka, India - Shabadi, Nayanabai; Anil, Deepak; A., Vanmathi; Hegde, Saurish; L., Nagendra; B. N., Kruthika; Salkatte, Ravindra; D., Sunil Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: Agriculture, being the main source of livelihood in most parts of the country, has some hidden dangers to the farmers which get them injured or ill. Methods: A community-based cross-sectional study was conducted for 2 months among farmers aged >18 years of age residing in rural Mysuru. A purposive sampling technique was used and the data was collected from 150 farmers through house-to-house interviews using a pre-tested structured questionnaire. Results: The survey took account of the farmer’s opinion on first aid procedures; a vast majority of the practices weren’t supported by any scientific evidence. Ineffective first-aid procedures could worsen the problem. Thus, the farmers should receive sufficient first aid training and education, enabling them to take appropriate action for themselves and their communities in an emergency. Conclusions: The survey took account of the farmer’s opinion on first aid procedures; a vast majority of the practices weren’t supported by any scientific evidence. Ineffective first-aid procedures could worsen the problem. Thus, the farmers should receive sufficient first aid training and education, enabling them to take appropriate action for themselves and their communities in an emergency.